The Hijrah to Yathrib as a Socio-Political Strategy in the Formation of the Early Islamic Political Order - Ridwan Nasution; Abdul Rahman; Muhammad Zein (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2026)
The Prophet’s migration (Hijrah) to Yathrib is generally understood within a theological framework as an effort to preserve the Islamic mission from the pressures of the Quraysh. While this perspective is important, it tends to overlook the socio-political dimensions underlying the choice of Yathrib as the destination of the migration, rather than other regions in the Arabian Peninsula. This article aims to analyse the Hijrah to Yathrib from a socio-political perspective by positioning it as a strategic decision within the context of social structure, political conflict, and the need for political legitimacy. This study employs a qualitative-descriptive approach based on a literature review of sirah sources, classical Islamic historiography, and modern academic scholarship. The findings indicate that Yathrib possessed a relatively open socio-political character, marked by fragmented power structures, ethnic and religious plurality, and a crisis of local leadership legitimacy, which enabled the emergence of an external authoritative figure such as the Prophet Muhammad. These conditions suggest that the Hijrah was not merely a geographical relocation, but rather a transformative process from a tribal-based society into a political community bound by a shared legal agreement. This article contributes to the enrichment of Hijrah studies by offering an alternative interpretation that frames the migration as an early form of socio-political transformation in Islamic history.